PENGUATAN PENGEMBANGAN SOSIAL EKONOMI (PSE) SEBAGAI UPAYA PENGENTASAN KEMISKINAN - Taek, Petrus Ans Gregorius; Wisadirana, Darsono; Sobari, Wawan (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
This qualitative case study aims to assess the contribution of the PSE Commission in alleviating poverty and to analyze PSE institutional strengthening in the success of poverty alleviation priority programs. Institutional strengthening is the key to the sustainability and success of poverty alleviation programs. However, there are studies that show that institutional strengthening through legal aspects, Provincial Drinking Wages and public policies have been effective enough to alleviate poverty. Of the many findings that exist, researchers discovered new things, namely through institutional strengthening in aspects; Structure, HR, Finance, Organizational Funding and Assets, Monitoring and Evaluation, Legality, Data and Information and Collaborative Networks can determine the success of the institution in alleviating poverty and the sustainability of poverty alleviation priority programs. The pattern of the empowerment approach carried out by the government is seen as less touching on the problems of the poor because it is project oriented, while the one carried out by the Catholic Church is oriented towards religious values.